Hellenistic land battles 300-167 BCE : a history and analysis of 130 engagements - Ray, Fred Eugene, Jr., 1949- (McFarland and Company, Inc., 2020)
"The Hellenistic Period (323-31 BCE) saw the Grecian phalanx-long dominant in Mediterranean warfare-challenged by legionary formations from the rising city-state of Rome. The Roman way of war would come to eclipse phalanx-based combat by the 160s yet this was not evident at the time. Rome suffered numerous defeats against the phalanxes of Pyrrhus and Hannibal, its overseas campaign against the brilliant Spartan mercenary Xanthippus met disaster, and several Roman victories over Hellenistic foes were not decisive. The story of combat in this pivotal era is not well documented. This book for the first time provides detailed tactical analyses for all 130 significant land engagements of Hellenistic armies 300-167 BCE."